1987
DOI: 10.1128/aac.31.6.865
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical antibacterial activity of cefmenoxime against Proteus vulgaris

Abstract: The growth-inhibitory effect of cefmenoxime against Proteus vulgaris was studied by using the broth dilution and paper disk diffusion methods. Cefmenoxime showed growth-inhibitory activity against Proteus vulgaris at low concentrations but not at high concentrations up to a certain limit. This paradoxical antibacterial activity was not observed with cefoperazone and cefbuperazone. The induction of I8-lactamase by cefmenoxime and the rate of hydrolysis of cefmenoxime in the culture broth were proportional to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…However, several exceptions to this trend have been reported (3,9,13). In previous papers (4,5), we reported that some 7-aminothiazolyl-type cephalosporins showed paradoxically reduced activities against Proteus vulgaris when they were present at high concentrations. Indeed, it has been difficult to demonstrate such paradoxical antibacterial activity clinically, but it appears that the in vivo paradoxical effect can be confirmed by using an experimental infection model.…”
mentioning
confidence: 91%
“…However, several exceptions to this trend have been reported (3,9,13). In previous papers (4,5), we reported that some 7-aminothiazolyl-type cephalosporins showed paradoxically reduced activities against Proteus vulgaris when they were present at high concentrations. Indeed, it has been difficult to demonstrate such paradoxical antibacterial activity clinically, but it appears that the in vivo paradoxical effect can be confirmed by using an experimental infection model.…”
mentioning
confidence: 91%
“…P. vulgaris 11, a strain that has been described previously (4), and P. vulgaris 11-S, a P-lactamase-noninducing mutant of P. vulgaris 11, were used in this study. P. vulgaris 11-S was derived by mutagenesis with selection, based on its susceptibility to cephaloridine and ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…The P-lactamase activity was determined by the modified microiodometric method of Novick (8) for piperacillin or the spectrophotometric method (12) Induction activity for the ,-lactamase. The P-lactamaseinducing activity was determined by a previously described method (4). An overnight culture of P. vulgaris in sensitivity broth was diluted 20-fold with the same medium and incubated with shaking at 37°C for 2 h. Then, various concentrations of antibiotics were added as the ,-lactamase inducers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations